The Effectiveness of Animal Control Implementation According to Regional Regulation No.17 Of 2016 Concerning Public Order in South Bolaang Mongondow Regency - Suratman, Suratman; Djafar, Marwan; Nusa, Apriyanto (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
This study aims to analyze the effectiveness of the implementation of free-range animal control as stipulated in the Regional Regulation of South Bolaang Mongondow Regency Number 17 of 2016 concerning Public Order. The main problem studied was the extent to which the regulation was implemented effectively and the obstacles faced by local regulation enforcement officials in implementing these provisions. This study uses an empirical juridical approach method by collecting data through literature studies and interviews with Satpol PP officials and the local community. The results of the study show that the implementation of animal control has not run optimally due to the lack of human resources, supporting facilities, and low legal awareness of the animal owner community. In addition, weak supervision and sanctions enforcement are the main inhibiting factors. Therefore, a strategy of institutional capacity building, continuous socialization, and cross-sector collaboration is needed to support the enforcement of local regulations more effectively